The (il)legal limitation of women’s recruitment into Brazilian military police forces - Pivetta, Luciane B. D. (Policing and society, 2021)
The underrepresentation of women in law enforcement institutions is a global pattern. However, increasing awareness of gender inequality is stimulating the implementation of affirmative action policies to encourage women into policing, especially in developed countries. Despite this, Brazil is moving in the opposite direction. This study investigates the latest military police recruitment programmes of all Brazilian states, as well as the laws that regulate these processes. This research shows that 74% of the latest recruitment programmes explicitly restricted the selection of female officers to a maximum threshold. Therefore, instead of promoting diversity, recruitment has imposed barriers to female integration, widening the gender gap in police forces. Moreover, this unjustifiable limitation violates the rights to equality and non-discrimination, protected not only in the Brazilian Federal Constitution of 1988 but also in several international conventions ratified by Brazil.